Efficient Exploitation of Multiple Novel Bacteriocins by Combination of Complete Genome and Peptidome - Yi, Lanhua; Luo, Lingli; Lü, Xin (Frontiers in Microbiology, 2018)
Backgroud: The growing emergence of antibiotic-resistant pathogens including the most dangerous superbugs requires quick discovery of novel antibiotics/biopreservatives for human health and food safety. Bacteriocins, a subgroup of antimicrobial peptides, have been considered as promising alternatives to antibiotics. Abundant novel bacteriocins are stored in genome sequences of lactic acid bacteria. However, discovery of novel bacteriocins still mainly relies on dubious traditional purification with low efficiency. Moreover, BLAST is invalid for novel bacteriocins which have no/low homology to known bacteriocins in databases. Therefore, an efficient, simple, universal and time-saving method was needed to discover novel bacteriocins. Methods and Results: Crude bacteriocins from both cell-related and culture supernatant of Lactobacillus crustorum MN047 fermentation were applied to LC-MS/MS for peptidome assay, by which 131 extracellular peptides or proteins were identified in the complete genome sequence of L. crustorum MN047. Further, the genes of suspected bacteriocins were verified by expressed in E. coli BL21 (DE3) pLysS. Thereafter, eight novel bacteriocins and two nonribosomal antimicrobial peptides were identified to be broad-spectrum activity against both Gram-positive and Gram-negative bacteria, including some multidrug-resistant strains. Among them, BM1556 located within predicted bacteriocin gene cluster. The most active bacteriocin BM1122 had low MIC values of 13.7 mg/L against both S. aureus ATCC29213 and E. coli ATCC25922. The BM1122 had bactericidal action mode by biofilm-destruction, pore-formation and membrane permeability change. Conclusions: The combination of complete genome and peptidome is a valid approach for quick discovery of novel bacteriocins without/with-low homology to known ones. This method will contribute to deep exploitation of novel bacteriocins in genome of bacteria submitted to GenBank.